Portable Force Plates: A Viable and Practical Alternative to Rapidly and Accurately Monitor Elite Sprint Performance - Irineu Loturco; Lucas A. Pereira; Ronaldo Kobal; Cesar C. Cal Abad; Victor Fernandes; Rodrigo Ramirez-Campillo; Timothy Suchomel (MDPI AG, 2018)
This study aimed to examine the associations between a series of mechanical variables automatically generated by a portable force plate (PFP) and the actual performance of professional sprinters over a 150 m course. To test these correlations, 12 top-level sprinters performed vertical jumps (squat and countermovement jumps; SJ and CMJ, respectively), a 60 m sprint test, and a 150 m sprint test. Pearson product-moment coefficient of correlation and multiple regression analyses were used to determine the relationships between the sprinting velocities and vertical jump outputs. The SJ parameters were moderately to near perfectly associated with the different sprint distances, and the SJ height presented the highest correlation scores (r = 0.90 with velocities over 10- and 20-m). The correlation coefficients between the CMJ outcomes and sprint results varied between moderate and very large (from 0.38 to 0.88). Finally, the coefficients of determination (R2) ranged from 0.71 to 0.85 for the different multiple regressions involving PFP automatic measures. The PFP can provide practitioners with quick and accurate information regarding competitive athletes. Due to the strong correlations observed, coaches are encouraged to frequently adjust and tailor the training strategies of their sprinters, using practical and timesaving PFP measurements.